Observation of Defects in Aluminum 6061 Castings Using Dye Penetrant Testing with Varied Pouring Temperatures - Zhafir, Ammar (Yayasan Kawanad, 2024)
Aluminum 6061, an Al-Mg-Si alloy, exhibits excellent extrudability. The study examines casting defects under pouring temperatures of 700°C, 750°C, 800°C, and 850°C. Aluminum is melted in a gas furnace and poured into a mold designed for the Constrained Rod Casting (CRC) method. Dye penetrant testing identifies surface defects, such as cracks and porosity, using colored penetrant fluids to reveal discontinuities. Results indicate that pouring temperature significantly affects defect type and severity. At 700°C, minor porosity is observed with minimal surface issues. Conversely, at 850°C, linear cracks exceeding 1.5 mm and extensive porosity appear, attributed to high thermal contraction and uneven solidification. An optimal pouring temperature range for Aluminum 6061 minimizes defects while maintaining casting quality.